Monitoring and Suppression Strategies of the Interharmonic in the Grid-Connected Photovoltaic System: A Review - Mingxuan Mao; Yuhao Tang; Jiahan Chen; Zhao Xu; Haojin Sun; Chengqi Yin (Energies)
With the continuous advancement of the green and low-carbon transformation of energy structures in countries around the world, renewable energy sources such as solar energy are receiving increasingly widespread attention. Driven by this trend, photovoltaic (PV) power generation, with its unique advantages, has continuously increased the scale of PV grid connection. However, the inherent characteristics of solar energy and the control features of grid-connected PV systems result in the presence of a large amount of interharmonic components in their output current, seriously endangering the safety and stable operation of the power system. Since interharmonics are difficult to obtain in an intuitive way, this paper first introduces the monitoring methods of interharmonics. Based on accurately monitoring the interharmonics, further discussions were carried out around the interharmonic suppression strategies. Through the analysis of the advantages and disadvantages of various interharmonic monitoring methods and suppression strategies, guidance can be provided for the selection of interharmonic monitoring methods and suppression strategies in different scenarios.